Thermal Expansion and Hydrostatic Pressure Experiment Using Common Materials for Supporting Science Education in a Rural Area at Central Sulawesi, Indonesia (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2019)
Experiments are needed in science learning. However, the instruments used cost high; thus, it is difficult to find, especially in rural areas. The purpose of this study was to develop a low-cost tool for science learning. This science experiment has been successfully developed from inexpensive common materials. Research and Development design employing Gall and Borg Model was used in developing the science instruments. Analysis, design, fabricate, validate, revising, and implementation were the steps in producing the devices. Observation sheet and questionnaire were used for evaluating and validating the instrument. The subject of this study was students of SMPN 1 Sigi, Sigi Sub Province, Central Sulawesi.Â After designed and fabricated, the devices were validated by two judges to know the practicality and convenience. The tools were set up to demonstrate the expansion concept of gas and liquid; also, to establish the presence of hydrostatic pressure inside the fluid. The N-gain analysis was performed to know the increase of student understanding after employing the instruments in science learning. The results showed that student understanding was increased by about 30.13% after using devices in science learning. In other words, the designed tools were succeeded in introducing the concept of gas and liquid well and in establishing the fact that the higher hydrostatic pressure of the fluid is discovered in a deeper location inside the liquid. Based on the success, the devices were socialized to other science teachers in the area.